Description of the larva of Gynacantha millardi Selys, 1891 (Odonata: Aeshnidae) from Chhattisgarh, India - Dawn, Prosenjit; Chandra, Kailash (Zootaxa, 2016)
The larva of Gynacantha millardi Selys is described here from female larvae and male and female exuviae collected from Chhattisgarh, India. Unlike other Gynacantha larvae known so far, G. millardi has 7 palpal setae almost equal in length; in other species, the palpal setae are of different lengths. The larvae lack a tooth on each side of the median cleft and have a distinct blunt tooth on the inner margin corner of each labial palp. The larvae were found in a semi-stagnant forest pool with enormous growth of aquatic vegetation.